Oxidative conditions along the continental shelf of the Southeast Pacific during the last two millennia: a multiproxy interpretation of the oxygen minimum zone variability from sedimentary records - Muñoz, Praxedes; Castillo, Alexis; Valdés, Jorge; Dewitte, Boris (Frontiers in Marine Science, 2023)
The oxygen minimum zone (OMZ) is an essential feature along the Pacific margin, extensively studied for its influence on benthic fauna, acquiring relevance in coastal zones due to its impact on aquaculture species, marine-managed areas, and marine-protected areas. The most evident temporal variability beyond seasonal timescales observed for the OMZ was related to inter-annual variability associated with El Niño, when warmer and more oxygenated waters arrive at shallower zones and the OMZ becomes deeper. However, the impact of oxygen-deficient water that appears sporadically over the shelf is not yet understood. This study provides an integrated view of the oceanographic and climatic conditions behind bottom oxygen conditions along the Chilean continental margin, considering the temporal variability in the South East (SE) Pacific during the last ~2000 years. We organized the information on redox-sensitive metals and δ15N from sedimentary cores obtained from shelf zones from 23°S to 36°S at water depths lower than 100 m. The results demonstrate the variability in the upper part of the OMZ over the shelf, which seems to respond to climatic oscillations. The element distribution indicated in particular a more intense OMZ was developed over the shelf before 1400 AD, followed by more oxygenated bottom conditions afterward, except between 1925 and 1970 off 36°S when the OMZ was intensified, a condition that was not observed at the northern sites. This period mostly coincided with a low Pacific Decadal Oscillation amplitude and reduced El Niño Southern Oscillation (ENSO) activity. In the last 50 years, the proxy data suggests less intense suboxic environment along the Chilean margin. This weakening of the upper boundary of the OMZ in the last decades is interpreted as resulting from the accumulative effect of ventilation processes at different time scales.